К систематике и синонимии комаров-лимониид Limnophila posthabita и L. tetrasticta (Diptera, Limoniidae) - Савченко, Е.Н. (Вестник зоологии, 1982)
As proved on the base of the tvoes examination the Limoniid-fly Limnophila posthabita B e r g r o t h , 1888, was to be transferred in the genus Dactylolabis O.-S. and the Limoniid-fly Limnophila tetrasticta B e r g r o t h , 1888,- in the Genus Pseudolimnophila Al. Correspondinglythe following synonymyis established: Dactylolabis (? Coenolabis) posthabita ( B e r g r o t h, 1888), comb. nova = Limnophila posthabita B e r g roth, 1888, and Pseudolimnophila lucorum (Miegen, 1818) = Pseudolimnophila tetrasticta (Bergroth, 1888), comb. et syn. nov.